Pacing across the membrane: the novel PACE family of efflux pumps is widespread in Gram-negative pathogens - Hassan, Karl A.; Liu, Qi; Elbourne, Liam D.H.; Ahmad, Irshad; Sharples, David; Naidu, Varsha; Chan, Chak Lam; Li, Liping; Harborne, Steven P.D.; Pokhrel, Alaska; Postis, Vincent L.G.; Goldman, Adrian; et al. (Research in microbiology, 2018)
The proteobacterial antimicrobial compound efflux (PACE) family of transport proteins was only recently described. PACE family transport proteins can confer resistance to a range of biocides used as disinfectants and antiseptics, and are encoded by many important Gram-negative human pathogens. However, we are only just beginning to appreciate the range of functions and the mechanism(s) of transport operating in these proteins. Genes encoding PACE family proteins are typically conserved in the core genomes of bacterial species rather than on recently acquired mobile genetic elements, suggesting that they confer important core functions in addition to biocide resistance. Three-dimensional structural information is not yet available for PACE family proteins. However, PACE proteins have several very highly conserved amino acid sequence motifs that are likely to be important for substrate transport. PACE proteins also display strong amino acid sequence conservation between their N and C-terminal halves, suggesting that they evolved by duplication of an ancestral protein comprised of two transmembrane helices. In light of their drug resistance functions in Gram-negative pathogens, PACE proteins should be the subject of detailed future investigation.